(untitled) (Journal of Analytical Oncology, 2017)
One of the hotspots in clinical research today is molecular genetic analysis of structural DNA alterations. Working with DNA obtained from formalin-fixed and paraffin-embedded (FFPE) tissue specimens is particularly challenging, due to cross-linking and fragmentation of DNA. We performed a comparative analysis of DNA extraction methods from FFPE tissue using two in-house protocols and Qiagen (QIAamp DNA FFPE Tissue Kit) and Roche (High Pure FFPET DNA Isolation Kit) commercial kits presented in the Russian market and used in clinical practice. To assess the quantity and quality of the isolated DNA, we used the real-time PCR to rate DNA yield, the inhibited impurity content and the degree of fragmentation. Our findings may be useful for a medical laboratory that performs testing of somatic mutations for the targeted therapy selection, and researchers who specialized in tumor genome structure studies in respect to patient prognosis and prediction of the sensitivity or resistance of tumor cells to therapy.